Impacto do uso do simbiótico no desenvolvimento da doença hepática gordurosa não alcoólica (DHGNA) em ratos - Tagliari, Eliane (2015)
OBJECTIVE: To determine whether the modulation of intestinal microbiota with the use of symbiotic alter the development of non alcoholic fat liver disease (NAFLD). METHODS: 45 adult male Wistar rats were used, males with 200 grams for this experimental study. The animals were divided into 4 groups: G1 = control diet; G2 = Control + symbiotic; G3 = Hypercaloric + symbiotic; G4 = Hypercaloric. After 60 days the animals were euthanized. Blood was collected for biochemical analysis, IL6 dosage and histological analyzes of the intestine and liver. RESULTS: The symbiotic did not influence the weight gain or the alimentary efficiency coefficiency (CEA) in G3 and G4. The G2 had greater weight gain and the G1 had a higher CEA. G1 had the highest expression ALT (150±35 in G1 vs. 75±5 in G2, p<0,001; vs 62±5 in G3 p<0,001). The group (G4) had ALT greater expression (62.1 ± 5 in G3 vs 95.6 ± 8.6 in the G4, p = 0.104). Regarding AST, G1 mass increased AST (165 ± 23in G1 vs 94 ± 6 in G2, p = 0.001) and (G4) was higher expression of AST (78 ± in G3 vs 141 ± 9.7 in G4 P <0.002). The groups that used the symbiotic (G2 and G3) had a lower variation of ALT / AST. Liver histology showed different stages of NAFLD among all groups. In groups G2 and G3 10% of the animals that have evolved to severe steatosis. The dosage of IL-6 when compared G3 (104.0 ± 15.31 (p <0.028)) x G4 (240.58 ± 53.68, p <0.007) showed that the G4 had greater expression of serum IL- 6. Among the G2 (124.0 ± 13.80) vs G3 (104.0 ± 15.31) there was no statistical difference compared to IL-6 expression, p <0.389. CONCLUSION: The symbiotic can be an alternative for preventing and treating NAFLD, according to the results was able to reduce the hepatic aminotransferase activity and reduce the expression of IL6. But contrary to biochemical analysis, histology showed that the symbiotic was unable to prevent the severity of NAFLD in rat.